Pengaruh Viral Marketing, Citra Merek dan Gaya Hidup terhadap Keputusan Pembelian Produk Hand And Body Lotion Merek Nivea (Studi Kasus pada Mahasiswa Fakultas Ekonomi Universitas 17 Agustus 1945 Banyuwangi) - Puspitasari, Bela Ayu; Sudirman, Rio; Purnomo, Endri (Neolectura, 2024)
This research aims to determine and analyze the influence of Viral Marketing, Brand Image and Lifestyle on Purchase Decisions for Nivea brand hand and body lotion products. The research population was students from the Faculty of Economics, University of 17 August 1945 Banyuwangi, with a research sample of 65 respondents. With the data obtained using the Probability Sampling technique with a simple random sampling technique and carrying out analysis which includes instrument testing, classical assumption testing, multiple linear regression testing, hypothesis testing and coefficient of determination testing. Based on the results of the analysis, conclusions can be drawn from the results of the hypothesis test F test, the Viral Marketing, Brand Image and Lifestyle variables are stated to be good and have a significant effect on the Purchase Decision variable for Nivea brand hand and body lotion products. The results obtained include validity and reliability, all of which are suitable for use and can be used in further tests. The regression results obtained Y = 4.004 + 0.364X1 + 0.366X2 + 0.334X3, the simultaneous test obtained calculated F> F table, t test for all variables calculated t value> t table, the value of the Adjusted R Square coefficient of determination was 40.8%, Assumption test The classic includes the normality test for all normal variables, the multicollinearity test without all multicollinearity, the total heteroscedasticity test without heteroscedasticity.